Tree survey of Ceci Cunha avenue and central squares of the municipality of Arapiraca, AL / Levantamento arbóreo da avenida Ceci Cunha e praças centrais do município de Arapiraca, AL - Rosane Maria dos Santos Silva; Lucinelma dos Santos Silva; Dacio Rocha Brito; Rafael Lima Vieira dos Santos; Iracema Raquel Santos Bezerra; Luan Lucas Cardoso Lima (Universidade Estadual de Alagoas, 2019)
Urban arborization is considered the set of native and exotic plants cultivated in public or private urban areas, then it is appropriate to plan and direct to adapt to the physical space, bringing knowledge and comfort to the community. It is also appropriate to choose species keeping biodiversity on site with native and or adapted plants, and to verify projects already installed and their suitability with the environment and the desires of the community, especially in cities in full development, with strong growth and that without planning will cause future problems to the community. The objective was to identify the species planted in the main urban areas of Arapiraca, Alagoas, Brazil, considered the metropolis of the future, seeking to know the diversity of plants, their use in environmental education, and contribute to the maintenance of the arborization existing or even suggest interventions, integrating economic development, community and public interest, enabling better conditions to promote the quality of life of the population. Thus, quali-quantitative surveys of the plants located on the main avenue of the city, Avenida Ceci Cunha, in Largo Dom Fernando Gomes and in the squares Marques da Silva, Luiz Pereira Lima and Manoel André were carried out. The most found species on Avenida Ceci Cunha were Wodyetia bifurcata A. K. Irvine and Erythrina velutina Willd. In general, the species Roystonea oleracea (N. J. Jacquin) O. F. Cook and Bauhinia foricata Link were found in the most frequent squares. It was observed that the maximum percentage of each species is within the recommended or very close to urban arborization, which is 15%. It is also concluded that the arborization found does not affect the local structure or the passers-by.